Digital Health Literacy About COVID-19 as a Factor Mediating the Association Between the Importance of Online Information Search and Subjective Well-Being Among University Students in Vietnam - Nguyen, Linh Hoang Thuy; Vo, Man Thi Hue; Tran, Lien Thi Mai; Dadaczynski, Kevin; Okan, Orkan; Murray, Linda; Van Vo, Thang (Frontiers in Digital Health, 2021)
Introduction: Digital health literacy (DHL) has recently been proposed as a means of enabling healthy decisions for protective behavior, preventive measures and adherence with COVID-19 policies and recommendations especially in the era of the “infodemic”. This study aimed to (1) identify COVID-19 related DHL and its association with online information seeking; (2) to elucidate COVID-19 related DHL as mediator predictor between the importance of online information search and its association with subjective well-being among Vietnamese university students. Methods: A cross-sectional web-based survey was used to elicit the responses of Vietnamese students over 2 consecutive weeks (from April 25th to May 9th, 2020, n=1,003, 70.1% female, mean age 21.4  3.1). The online survey questionnaire collected data on participants’ sociodemographic characteristics, DHL about COVID-19, information seeking behavior and subjective well-being. Mediation analysis was conducted using the importance of searching COVID-19 related information as independent variables, subjective well-being as a dependent variable and DHL as mediator variable. Results: Among 1,003 students, the mean (SD) of DHL related to COVID-19 was 2.870.32. 87.2% of the students reported sufficient well-being, while almost 13% reported low or very low well-being. The findings also indicated that search engines were the most popular platform for information seeking by Vietnamese students (95.3%) and 92.8% of participants had searched for information related to the current spread of COVID-19. Not searching for hygiene regulation as part of infection control, and an average level of information satisfaction were associated with limited DHL (p<0.05). The importance of online information searching related to COVID-19 increased student’s subjective well-being significantly and also limited DHL (p<0.05). DHL was found to mediate the relationship between the importance of online information searching and students’ subjective well-being. Conclusion: The finding provides insight into DHL about COVID-19 among university students, and their ability to find, understand, appraise and use online health related information during lockdown throughout the first COVID-19 pandemic wave. DHL should be highlighted as a mediating factor that enhances the positive effect of the importance of information seeking on psychological well-being. However, further studies are needed to better define the mediating role of DHL across others factors.